2000
DOI: 10.1046/j.1440-1789.2000.00281.x
|View full text |Cite
|
Sign up to set email alerts
|

Dural band pathology in syringomyelia with Chiari type I malformation

Abstract: Surgical material taken from the 'outer layer' of thickened dura mater (dural band) at the craniovertebral junction of eight cases of syringomyelia with Chiari type I malformation was histologically examined in comparison with four autopsy cases as controls. The dural band was thickened and there were increased numbers of collagen fibers which showed fiber splitting, hyalinous nodule, calcification and/or ossification. These changes were not observed in the four control cases. Thus, it is suggested that the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 21 publications
2
33
1
Order By: Relevance
“…Also, we worked on donors from the Ecole de Chirurgie Assistance Publique -Hopitaux de Paris whom we considered to be free of CM-I. We know from Nakamura et al 30 that DM in CM-I can be thicker than a normal dura. This implies of course that the neurosurgeon must remove a significant thickness of dura to obtain a visual deformation of the split area and then a satisfying decompression.…”
Section: Discussionmentioning
confidence: 99%
“…Also, we worked on donors from the Ecole de Chirurgie Assistance Publique -Hopitaux de Paris whom we considered to be free of CM-I. We know from Nakamura et al 30 that DM in CM-I can be thicker than a normal dura. This implies of course that the neurosurgeon must remove a significant thickness of dura to obtain a visual deformation of the split area and then a satisfying decompression.…”
Section: Discussionmentioning
confidence: 99%
“…45 Compared with healthy controls, the authors found an increase in collagen fibers, hyalinous nodules, and calcification in the dural band of patients with Chiari I malformation. The success of the decompressive procedure should be confirmed using intraoperative ultrasonography and further decompression should be performed if the ultrasonographic findings prove it to be inadequate.…”
Section: Surgical Approachmentioning
confidence: 90%
“…There are several theories that have been developed to explain both the cerebellar tonsillar descent and the frequently associated syringomyelia. [1][2][3]5,7,8,17,26,28,37,41,42,[44][45][46][47]51,53,55 Analysis of the data in the literature suggests several factors: 1) the ratio of the posterior fossa neural element volume to posterior fossa cranial volume is increased. This is related to either an underdeveloped occipital somite originating from the paraaxial mesoderm, which results in a smaller posterior fossa, or to an overgrowth of the supratentorial component and consequent shallow posterior fossa.…”
mentioning
confidence: 99%
“…Patients with CM-I demonstrate a thickened dural band at the craniovertebral junction, with histological evidence of hyalinosis, calcification, and/or ossification. 18 To restore CSF dynamics, surgical decompression is sought, with the mainstay of therapy being a posterior intradural decompression. In this case series, we demonstrate that an extradural decompression may be appropriate for increasing the important CSF spaces such that there is an improvement in CSF dynamics and consequently neurological symptoms.…”
Section: Discussionmentioning
confidence: 99%